Modeling the Interaction of Unmanned Aerial Vehicles in a Swarm as an Object with Distributed Parameters - Dyvak, Mykola; Spivak, Iryna; Dyvak, Taras; Kindzerskyi, Oleksandr (International Conference on Advanced Computer Information Technologies (Print), 2024)
Many scientific studies using unmanned aerial vehicle swarms were considered and the principles of control and interaction between swarm elements were analyzed (the models of swarm behavior, the motion coordination model, the decision-making models). An approach to the management of unmanned aerial vehicle swarms based on an algorithm is proposed, which will allow, by changing only part of the parameters of the elements, to adjust all other elements of the swarm. The feasibility of developing a mathematical model of characteristics of unmanned aerial vehicle swarm as objects with dispersion parameters is demonstrated. The article describes the proposed approach for the synthesis of mathematical models of the characteristics of swarm elements as objects with dispersion parameters using structural-parametric analysis. The validation of the model is carried out on the basis of obtained data in the specified observation area, and the adequate prognostic features of the model are confirmed.